2004
DOI: 10.1177/153331750401900306
|View full text |Cite
|
Sign up to set email alerts
|

Documenting pathways to dementia care: Relative validity of questionnaire, interview, and medical record formats

Abstract: One of the shortcomings of the pathways-to-care literature is the lack of empirical support for the validity of the data collection methods. This study uses three common formats to collect retrospective pathways-to-care data for adults who have been diagnosed with possible or probable Alzheimer's disease (AD) and compares indicators to evaluate their relative validity. Forty family caregivers of adults diagnosed with possible or probable AD were recruited from the caregiver registry of the Boston University Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…As for the findings related to sources of help, the studies in this review consistently showed that close family members-especially spouses and children-were the first choice of a source of help 16,[26][27][28][29][30] ; followed by the family physician. The most common professional or formal source of help included in the reviewed studies was primary physicians, followed by specialists such as neurologists and psychiatrists.…”
Section: Dimensions and Hs Typementioning
confidence: 72%
“…As for the findings related to sources of help, the studies in this review consistently showed that close family members-especially spouses and children-were the first choice of a source of help 16,[26][27][28][29][30] ; followed by the family physician. The most common professional or formal source of help included in the reviewed studies was primary physicians, followed by specialists such as neurologists and psychiatrists.…”
Section: Dimensions and Hs Typementioning
confidence: 72%
“…Previous investigations have not triangulated clinician, patient and carer perspectives of diagnostic pathways to clarify factors contributing to the time to diagnosis in YOD. Data collection techniques (questionnaire, structured interview, medical records) have varied in dementia pathway research with structured interviews and medical record review being most reliable (Drebing et al, 2004). Previous Australian studies have also been convenience samples (Luscombe et al, 1998;Speechly et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[16] attempt to establish the validity of the three most commonly used methods to study dementia care namely questionnaire, structured interview, and medical record review. We used snowballing and key informant contacts to trace epilepsy patients in the community.…”
Section: Discussionmentioning
confidence: 99%